Hoping for community in a technologically decelerated world - a critical utopian approach - Bock, Annekatrin; Macgilchrist, Felicitas; Rabenstein, Kerstin; Wagener-Böck, Nadine (Universität Vechta, 2024)
Against the backdrop of technological acceleration during the Covid-19 pandemic, this paper addresses how educational practitioners’ hopes articulate a critique of the present and simultaneously give voice to (im)possible futures. Drawing on Bloch’s "principle of hope" (1995), Appadurai’s "traces of future" (2021) and Levitas’ "utopia as method" (2013), we utilize a critical utopian approach inspired by Mu˜noz (2009). We interviewed educational practitioners who worked with young people during the pandemic, and identify three themes articulating our interviewees’ hopes for technologically decelerated futures: 1) young people’s participation in decision-making, which is linked to the wish for more visibility for young people in the future; 2) mutual care, which is interwoven with the wish for support in young people’s lives to be more reliable; 3) appreciation for other groups, opinions and ways of life, which is linked to the wish for more future interpersonal understanding. These three themes point to an overarching desire for solidarity in community which needs time, occasions, role models and spaces of encounter. We discuss the priority of technologically decelerated hopes and conclude with implications for future research that brings together imaginations of futures, observations of practical action and designs for future artefacts.
Diese Studie wurde im Rahmen der Fördermaßnahme "Corona Crisis and Beyond" von der VolkswagenStiftung gefördert [Förderkennzeichen Az 98893].
Keywords: Hope; Future education; Futures-making; Utopian methodology; Educational technology; Acceleration; Deceleration; Solidarity; Community; Sozialwissenschaften::370 Bildung und Erziehung::370 Bildung und Erziehung